Relationships between running demands in soccer match-play, anthropometric, and physical fitness characteristics: a systematic review - Aquino, R.; Carling, C.; Maia, J.; Vieira, L. H. P.; Wilson, R. S.; Smith, N.; Almeida, R.; Goncalves, L. G. C.; Kalva-Filho, C. A.; Garganta, J.; Puggina, E. F. (International Journal of Performance Analysis in Sport, 2020)
The aim of this study was to systematically review the current literature that has investigated the relationships between anthropometric and physical fitness characteristics and match-play running demands in female and male soccer players at youth and senior levels. Using PRISMA guidelines, four databases were searched: PubMed/NCBI, Web of Science and SPORTDiscus. Twenty-seven articles were selected resulting in a sample of 991 players (687 youth and 304 senior). Three studies related anthropometric measures to running demands during the matches and reported poor relationships (R2 = 4-36%). Incremental treadmill tests performed in laboratory settings showed large-to-very large correlations with total distance covered and/or high-intensity running activity during matches (R2 = 20-50%). Values for the Yo-Yo Intermittent recovery test levels 1 and 2 were associated with total distance covered and high-intensity running activity across all studies. This study collected scientific evidence that can aid sport science and coaching practitioners in understanding the construct validity of anthropometric and laboratory- and field-based assessments.